Odpowiedzi

Najlepsza Odpowiedź!
2009-11-12T20:02:38+01:00
A) (x + 1) (x + 2)( x + 3)= (x²+2x+x+2)(x+3)= x³+2x²+x²+2x+3x²+6x+3x+6= x³+6x²+11x+6
b) (x - 2 ) (x + 5) (2x - 1)= (x²+5x-2x-10)(2x-1)= 2x³+10x²-4x²-20x-x²-5x+2x+10=2x³+5x²-23x+10
c) (x - 4) (x + 1)²=(x+4)(x²+2x+1)= x³+2x²+x+4x²+8x+4=x³+6x²+9x+4
d) (2x - 3)²(x + 2)= (4x²-12x+9)(x+2)= 4x³-4x²-15x+18
2009-11-12T20:18:03+01:00
A)(x + 1) (x + 2)( x + 3)=
=(x²+2x+x+2)(x+3)=
=(x²+3x+2)(x+3)=
=x³+3x²+3x²+9x+2x+6=
=x³+6x²+11x+6


b)(x - 2 ) (x + 5) (2x - 1)=
=(x²+5x-2x-10)(2x-1)=
=2x²-x²+10x²-5x-4x²+2x-10x+10=
=7x²-13x+10

c)(x - 4) (x + 1)² =
=(x - 4) (x² + 1²)=
=x³+x-4x²-4

d)(2x - 3)²(x + 2)=
=(2*x - 3)²(x + 2)=
=(2²*x² - 3²)(x + 2)=
=(4x²-9)(x+2)=
=4x³+8x²-9x-18